Investing in One Health: Turning vision into action on the ground - Vietnam Agriculture Newspaper; International Livestock Research Institute (International Livestock Research Institute, 2024)
In this video, Hung Nguyen, leader of the CGIAR One Health Initiative and ILRI’s Health Program, highlights the role of multisectoral cooperation in advancing the One Health approach worldwide. He stresses the need to operationalize One Health at the ground level to address urgent challenges like zoonoses, emerging infectious diseases, foodborne illnesses and antimicrobial resistance.